EVALUATION OF THE EFFICACY OF DEXMEDETOMIDINE IN COVID-19 DISEASE - Mamadiev Khusanboy Ganijonovich (Scholar Express Journals, 2023)
The coronavirus disease (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an ongoing global public health problem. Dexmedetomidine, sold under the trade name Precedex among others, is an anxiolytic, sedative and analgesic. Dexmedetomidine is notable for its ability to provide sedation without the risk of respiratory depression and can provide cooperative or semi-excitation.
Keywords: Coronavirus; drug; COVID-19; dexmedetomidine